Unternehmensgründungen, Innovation und Regionalentwicklung: Spin-off-Gründungen aus Unternehmen - Koch, Andreas (ERDKUNDE, 2005)
The integration of innovations into existing economic structures is an important pre-condition for their successful implementation. Especially newly founded firms - which are frequently carriers of innovations - are suffering difficulties in achieving an adequate integration. In this contribution, an empirical study about employee start-ups based upon the transfer of innovative ideas, products or technologies is presented. It will be shown how recently founded firms come up to have close links to their environment and how this integration is conducive not only to the success of the innovation inside the firm, but also to the effective implementation of innovations in regional economic systems.